Um sistema de gerenciamento da qualidade de experiência orientada à transmissão de vídeos para dispositivos móveis em redes sem fio - Orlewilson Bentes Maia (2015)
The present scenario indicates an increased access to multimedia content services, especially video on demand and IP television, by mobile devices capable of playing high-definition videos anywhere. However, the success of these services is closely related to the video quality perceived by the user, also known as the quality of experience (QoE). This work proposes a quality management system for video transmission to mobile devices. The video streaming systems are characterized as well as the elements of its architecture. The different forms of video quality evaluation and the techniques used to improve this quality are described. Based on these studies, the development of a quality video manager for a streaming service on mobile devices is detailed, taking into account information about the transmission, the mobile device and the video encoding. As the video encoding choice is performed in the streaming server, this management does not overload the mobile device. For its operation, two predictors are required: one for the encoding choice, at the beginning, when the content is chosen; another for the automatic adjustment of the video quality according to the information collected during content playback on the mobile device. Several experiments were conducted for choosing the relevante features to be considered by these predictors. With a proposal of information treatment, an average improvement of 22% was achieved in the results, compared with Peak Signal-to-Noise Ratio (PSNR).